2017
DOI: 10.1186/s12906-016-1515-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-induced modulation of gene expression profile in human dermal fibroblasts: the effects of Thai herbal Sahatsatara formula, piperine and gallic acid possessing antioxidant properties

Abstract: BackgroundPain is the main symptom of most musculoskeletal disorders and can be caused by inflammation in association with oxidative stress. Thai herbal Sahatsatara formula (STF), a polyherbal formula, has been traditionally used for relieving muscle pain and limb numbness. This study aimed to investigate biologically active compounds of STF and its pharmacological effects related to antioxidant and anti-inflammatory activities.MethodsThe identification of possibly active compounds of STF was performed by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
2
12
0
1
Order By: Relevance
“…Since the flexibility to adjust the behavior to the new location of platform (new goal) or learning flexibility is closely related to the white matter function, so the better behavioral results in the reversal platform trial of MWM might support the protective effect of STF against the white matter injuries on learning flexibility. The protective effects of STF might come from piperine, the main active compound, that possesses antioxidant and anti-inflammation activities through the inhibition of ROS, TNF-α production and COX-2 expression [15,16]. Other ingredients in STF also have antioxidant, anti-inflammation, vasodilation and hemodynamic effects [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the flexibility to adjust the behavior to the new location of platform (new goal) or learning flexibility is closely related to the white matter function, so the better behavioral results in the reversal platform trial of MWM might support the protective effect of STF against the white matter injuries on learning flexibility. The protective effects of STF might come from piperine, the main active compound, that possesses antioxidant and anti-inflammation activities through the inhibition of ROS, TNF-α production and COX-2 expression [15,16]. Other ingredients in STF also have antioxidant, anti-inflammation, vasodilation and hemodynamic effects [21].…”
Section: Discussionmentioning
confidence: 99%
“…The certification and registration number of STF were G265/52 certified by FDA of Thailand with the recommended oral dose of 1.0-1.5 gm before meals, 3 times per day. The chemical determination was examined by thin-layer chromatography and high-performance liquid chromatography [15,21]. The fingerprint chromatograms and content determination of piperine in STF was determined (Figs.…”
Section: Preparation Of Sahatsatara Formula (Stf)mentioning
confidence: 99%
See 2 more Smart Citations
“…There were previous studies of STF demonstrated the fingerprint patterns of standard piperine compare with piperine in STF using thin layer chromatography (TLC), quadrupole time-of-flight mass spectrometry (QTOF) 4 . Furthermore, piperine was used for a quantitative marker by using high performance thin layer liquid chromatography (HPTLC) and ultra-performance liquid chromatography (UPLC) approaches 7 . However, only one compound is not enough to claim the clinical efficacy and mechanism of action of STF.…”
Section: Introductionmentioning
confidence: 99%